MILITATING IN FAVOR OF INTERNATIONAL HUMAN RIGHTS LAW (EVEN IN TIMES OF COVID-19 PANDEMIC) - Laura-Cristiana SPĂTARU-NEGURĂ (Challenges of the Knowledge Society)
Human rights have always been a concern for humanity. Delimitating the protection of human rights from other branches of law is necessary due to the similarity of the legal relations that are the object of certain different legal branches. Through the efforts supported globally by the means of the international jurisdictions, the global justice system can be more efficient. Although questions are constantly being raised about the fragmentation of law which would threaten the complex legal system created by the subjects of international law, we consider, however, that, at the level of human rights, we are witnessing a process of convergence, characterized by coherence and unity. The purpose of this study is to offer to the interested legal professionals and to the domestic authorities the information to adequately protect the right of each individual to respect for his or her rights under the international conventions. The study also tackles certain aspects regarding the application of human rights during COVID-19 pandemic, without alleging to be an extensive analysis of the subject.